Kebijakan Pemerintah Dalam Mewujudkan Ketahanan Pangan Di Indonesia - Rossi Prabowo (Universitas Wahid Hasyim, 2010)
Food security (food security) is a paradox and is more of a discoveryof the modern world. Food security should include the availability,distribution, and consumption. Agricultural development has a commongoal of promoting agribusiness, namely by building a synergistic andharmonious aspects: (1) upstream agricultural including seed, otherproduction inputs and agricultural machinery, (2) primary agriculture (onfarm),(3) agriculture downstream (processing), and (4) support servicesrelated to the advance of agribusiness. National Food Security must not beseparated from domestic food security / local. With reference to the matter,with the regional autonomy is expected to maximize the role of localgovernment in improving the agribusiness sector in achieving national foodsecurity. In addition, the restrictions on imported products is also one thingthat must be taken into consideration by the government, the diversificationof agricultural land into residential and industrial land is also a significantobstacle to the achievement of local and national food security, so it must bethe limit. Development of agriculture technology also is expected toimprove and streamline the agricultural sector. Diversification of FoodProduction in a way to diversify food consumption or to reduce the pressureon the availability of a range of food products, especially rice in Tunjangwith consumption patterns, The Role of Agricultural Research andDevelopment Agency were also in demand to provide new breakthrough tothe perpetrators in the agribusiness sector which will bring progress andrealization of national food security.